Impact of Multiple Sclerosis on Infertility and Impact of Infertility Treatments on Multiple Sclerosis Relapses in Slovenia: Medical Outline, Legal and Ethical Outcomes - Vrtačnik Bokal, Eda; Vrtačnik, Urban (Medicine, Law & Society, 2020)
Multiple sclerosis (MS) is an autoimmune inflammatory disorder of the central nervous system. It is common in the reproductive period and can lead to infertility and significant disability. The treatment on multiple sclerosis is recently more successful and enables better quality of life, therefore rising hope and desire for the future parents, also in terms of successful infertility treatments. In this context the couples should be managed concerning the detrimental effect of the disease itself on fertility, detrimental effect of the drugs used for treatment on gonads and in terms of the implementation of drugs used for ovarian stimulation and their impact on the basic disease (MS). Article finds solutions on the legal outcomes in situations where infertility treatments may negatively impact the progress of MS, as well as the solutions on how to (successfully) provide infertility treatments to the patients with MS. It proposes interdisciplinary approach between gynecologists and neurologists to perform required weighting of benefits and risks (burdens), deriving from specific action or treatment, whereas for the patients who shall not undergo infertility treatments due to their medical status, related to MS, it proposes storage of gametes under conditions, set by the law.